The Use of a Mini-Bioreactor Fermentation System as a Reproducible, High-Throughput ex vivo Batch Model of the Distal Colon - O’Donnell, Michelle M.; Rea, Mary C.; Shanahan, Fergus; Ross, R. P. (Frontiers in Microbiology, 2018)
Ex-vivo colon fermentation systems are highly versatile as models for analyzing gastrointestinal tract microbiota composition and functionality. Ex-vivo colon models range in size and functionality from bench-top micro fermenters to large units housed in individualized cabinets. The length of set-up time (including stabilization periods) for each fermentation system can range from hours to weeks to months. The aim of this study was to investigate a single-use cassette mini-fermentation system as a reproducible batch model of the colon. The online data log from the cassettes (triplicate wells across four different cassettes, n=12) was sensitive enough to identify real-time changes in pH, temperature, dissolved oxygen or liquid addition (sodium hydroxide) during the runs which could be addressed if an alarm set-point was triggered. The alpha diversity indices also showed little variation between cassettes with the samples clustering around the mean. The weighted beta diversity PCoA analysis illustrated that 95% of the variance between the samples was accounted for by the time-point and not the fermentation run/cassette used. The variation in taxonomic diversity between cassettes was limited to less than 20 out of 115 genera. This study provides evidence that micro-bioreactors provide some very attractive advantages as batch models for the human colon. We demonstrated a high level of reproducibility across fermentation cassettes when used in conjunction with a standardized fecal microbiota. The machine can operate 24 individual fermentations simultaneously and are relatively cost effective. Based on next generation sequencing analysis, the micro-bioreactors offer a high degree of reproducibility together with high-throughput capacity. This makes it a potential system for large screening projects that can then be scaled up to large fermenters or human/animal in vivo experiments.